P-ISSN 2086-7433 E-ISSN 2549-5801 DOI: doi.org/10.21009/JPD.XXX. ANALISIS KETERAMPILAN BERPIKIR KRITIS MELALUI PENDEKATAN PEMBELAJARAN STEAM PADA PESERTA DIDIK KELAS III DI SDIT RAUDHATUL JANNAH - Istikomah, Yusi; Andriana, Encep; Syachruroji, A. (Jurnal Pendidikan Dasar, 2024)
When learning is in the 21st century and technological developments are increasingly rapid, students are required to have 4C skills to face future challenges, one of the skills needed is critical thinking skills. Through education and learning is one provision for developing these skills, including through the application of the STEAM learning approach. This research aims to determine learning planning using the STEAM approach, the process of implementing learning using the STEAM approach and how students critical thinking skills use the STEAM approach. This research uses a qualitative approach, a descriptive method, where data collection uses data in the form of words and image. The results of the research show that the learning activities using the STEAM learning approach carried out by the teacher run according to the plans prepared in the RPP and carry out learning in accordance with the STEAM stages. The application of STEAM learning helps teachers develop critical thinking skills in students. Train students to form their own knowledge and solve problems during learning activities for class III students at SDIT Raudhatul Jannah.